A U-shaped copper-aluminum composite transition plate and its preparation method and application
By combining aluminum on the end face of the copper plate of the copper aluminum composite material on three sides and using explosive composite and heat treatment processes, the problem of difficult removal of oxide films in the existing copper aluminum composite material preparation methods and easy formation of hard and brittle intermediate compounds at the interface is solved, and a copper-aluminum composite transition plate with high binding strength and conductivity is achieved, which improves the connection reliability and safety.
Patent Information
- Application Number
- CN202410638571.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-05-22
AI Technical Summary
The existing methods for preparing copper-aluminum composite materials have problems such as difficulty in removing oxide films, easy formation of hard and brittle intermediate compounds at the interface, unstable welding quality, reduced conductivity and safety hazards.
The copper-aluminum composite transition plate designed with U-shaped structures realizes 100% metallurgical bonding of the copper-aluminum interface by combining aluminum on three sides of the end face of the copper-aluminum board, and adopts explosive composite and heat treatment methods, and controls intermetallic compounds at the bonding interface to improve binding strength and conductivity.
The high bonding strength and conductivity of the copper-aluminum interface are achieved, the connection reliability is improved, the resistivity is reduced, the safety hazards in traditional welding methods are avoided, and the process is simple and the cost is low.
Smart Images

Figure CN118385717B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper-aluminum composite transition plate, in particular to a U-shaped copper-aluminum composite transition plate, and also to a preparation method and application thereof, belonging to the technical field of materials. Background Art
[0002] Bimetallic composites can combine the excellent properties of each matrix metal to make up for the shortcomings of a single metal. They have the characteristics of high cost performance and low cost, and are currently a hot topic in the field of material research. As a typical bimetallic composite material, copper / aluminum layered composites have the advantages of high electrical conductivity and high thermal conductivity of copper and light weight, easy welding, low cost and corrosion resistance of aluminum. They have both excellent performance and cost economy and are widely used in power, heat transmission, new energy and other fields, and have attracted widespread attention from researchers at home and abroad. However, the main difficulties in preparing copper / aluminum bimetallic composites include: (1) Both copper and aluminum are easily oxidized, and the oxide film formed is difficult to remove; (2) A variety of hard and brittle intermediate compounds are easily formed at the interface, which endangers the performance of copper / aluminum bimetallic composites.
[0003] The existing methods for preparing copper-aluminum composite materials include rolling composite, casting and rolling composite, explosive composite, laser welding and friction welding. During the laser welding and friction welding process, a large amount of heat will be released for a long time, and a variety of continuous and dense intermediate compounds will be formed at the interface of copper and aluminum materials. With the subsequent operation under temperature conditions, the thickness of the intermediate compounds gradually increases, which not only makes the welding quality unstable, but also reduces the conductivity of the composite material. At the same time, welding defects such as unfusion, inclusions and pores are easily generated during the welding process, reducing the effective bearing area, causing stress concentration, reducing material strength, and easily causing corrosion, which can lead to safety accidents such as fire in severe cases. The biggest feature of the explosive composite method is that it can quickly and strongly weld metal materials with large differences in physical and chemical properties together, and can achieve metallurgical bonding between metal combinations that cannot be connected by other technologies. The interface bonding strength is high, but the explosive composite process parameters are difficult to control. If the charge is too low, the interface metallurgical bonding cannot be achieved and the bonding strength is low. If the charge is too much, it is easy to have too many and continuous intermetallic compounds at the interface. By adopting appropriate composite process parameters, the intermetallic compounds at the bonding interface can be effectively controlled.
[0004] In the graphitization furnace of the negative electrode material of the power energy storage battery, there are a large number of connections between the aluminum busbar and the copper busbar. The melting points of copper and aluminum are very different, and the surface is easily oxidized during welding. The traditional brazing or friction welding process is prone to produce a variety of brittle metal compounds, and the production cycle is long and the cost is high. The process parameters of the welding process are difficult to control, and the welding parts are prone to deformation or cracks. It is impossible to achieve full interface metallurgical bonding. The interface is prone to electrochemical corrosion, resulting in poor contact, affecting the conductive performance and even causing safety accidents such as fire.
[0005] The copper-aluminum composite transition plate is used for connecting the aluminum busbar and the copper busbar. For example, Chinese patent CN206461114 U discloses a copper-aluminum composite transition plate, which specifically includes an aluminum end for connecting with an aluminum material and a copper-aluminum composite end for connecting with a copper material. The copper-aluminum composite end includes an aluminum layer and an upper copper composite layer and a lower copper composite layer respectively composited on the upper and lower sides of the aluminum layer, and the ends of the upper copper composite layer and the lower copper composite layer close to the aluminum end are staggered along the length direction of the copper-aluminum composite transition plate. By staggering the ends of the upper copper composite layer and the lower copper composite layer close to the aluminum end on both sides of the aluminum layer, the defects of the copper-aluminum composite process are discretely distributed on both sides of the aluminum layer, reducing the influence of the copper-aluminum composite defects on the aluminum layer, improving the reliability and safety of the copper-aluminum composite transition plate, and not prone to fracture. The copper-aluminum composite plate is composited on both sides, with a total thickness of 2~12mm, and the thickness of the upper and lower copper composite layers is about 0.2~1.5mm, which cannot meet the use requirements of high current density connectors such as lithium-ion battery negative electrode materials in the field of new energy material technology. Summary of the invention
[0006] In view of the technical defects existing in the prior art, the first object of the present invention is to provide a U-shaped copper-aluminum composite transition plate. On the one hand, it has a U-shaped structural design. By composite aluminum on three sides of the end surface of the copper plate, metallurgical bonding can be achieved at three interfaces to form a bite structure, with high bonding strength and higher product connection reliability. On the other hand, by adopting explosive composite and heat treatment methods to realize the composite aluminum plate on three sides of the end surface of the copper plate, the bonding rate of the copper-aluminum interface reaches 100%, and at the same time, the intermetallic compounds at the bonding interface can be effectively controlled to achieve the purpose of improving the bonding strength, effectively reducing the resistivity, and increasing the conductivity. It is used for the transition connection between the aluminum busbar and the copper busbar. The U-shaped structure with three sides composite can convert the dissimilar metal welding mode of copper and aluminum into the same metal welding of aluminum and aluminum, copper and copper, thereby improving the connection reliability, realizing the direct connection between metal copper and aluminum, saving a large amount of metal materials, and improving the overall performance of the equipment while greatly reducing the cost.
[0007] The second object of the present invention is to provide a method for preparing a U-shaped copper-aluminum composite transition plate. The method realizes aluminum composite on three sides of the end surface of the copper plate by adopting explosive composite and heat treatment. The bonding rate of the copper-aluminum interface is high, and the intermetallic compounds of the bonding interface can be effectively controlled to achieve the purpose of improving the bonding strength, effectively reducing the resistivity, and increasing the conductivity. Compared with other existing composite methods, this method has obvious technical advantages, and does not require expensive equipment and a large number of operators, and has fast molding, high efficiency, low cost, stable quality and excellent performance.
[0008] The third object of the present invention is to provide an application of a U-shaped copper-aluminum composite transition plate, which is applied to the interface welding of aluminum and copper, especially for circuit connection. The U-shaped copper-aluminum composite transition plate is used for transition connection between the aluminum soft strip and the copper soft strip. It has the advantages of stable quality, high reliability, material saving, easy installation and use, simple production process, etc. It can be widely used in the connection of metal aluminum and copper in graphitization furnaces, transformers and other devices to achieve metallurgical bonding between metals, prevent electrochemical corrosion caused by direct connection between aluminum and copper metals, and prevent safety accidents. It can effectively solve the problem of fracture caused by the generation of various intermetallic compounds during traditional welding of copper and aluminum, thereby improving product quality and safety.
[0009] In order to achieve the above technical purpose, the present invention provides a method for preparing a U-shaped copper-aluminum composite transition plate, which comprises the following steps:
[0010] 1) After grinding and polishing the upper and lower surfaces to be composited at one end of the copper plate and the surface to be composited of the aluminum plate, an aluminum plate is assembled with the upper and lower surfaces to be composited of the copper plate in the manner of assembling the surfaces to be composited opposite to each other, an internal support is provided between the copper plate and the aluminum plate to ensure that the surface to be composited of the copper plate and the aluminum plate are at the same horizontal position, a buffer pad is laid on the back of the surface to be composited of the aluminum plate, explosives are evenly laid on the buffer pad, and the first explosive composite is detonated from the end of the surface to be composited of the aluminum plate to obtain a copper-aluminum composite plate;
[0011] 2) After the copper-aluminum end faces to be composited of the copper-aluminum composite plate and the surface to be composited of the aluminum plate are polished, the copper-aluminum end faces of the copper-aluminum composite plate are assembled with an aluminum plate in the manner of assembling the opposite faces of the surfaces to be composited, and an internal support is provided between the copper-aluminum end faces of the copper-aluminum composite plate and the aluminum plate to ensure that the copper-aluminum end faces of the copper-aluminum composite plate and the aluminum plate are at the same horizontal position, a buffer pad is first laid on the back of the surface to be composited of the aluminum plate, and then explosives are laid on the buffer pad in a gradient distribution method with the charge thickness gradually decreasing from the middle to the edge, and a second explosive composite is performed by detonating from the midpoint of the short side of the surface to be composited of the aluminum plate to obtain a U-shaped copper-aluminum composite plate;
[0012] 3) The U-shaped copper-aluminum composite plate is annealed to obtain.
[0013] The key to the technical solution of the present invention is to realize three-sided aluminum composite at one end of the copper plate by explosive composite combined with annealing treatment to form a copper-aluminum composite transition plate with a U-shaped structure. This U-shaped copper-aluminum composite transition plate can realize metallurgical bonding of three interfaces in the transition process of the copper-aluminum interface to form a bite structure, with high bonding strength and higher product connection reliability. The copper-aluminum composite process of the U-shaped copper-aluminum composite transition plate adopts explosive composite and annealing treatment, which can not only make the bonding rate of the copper-aluminum interface reach 100%, but also effectively control the intermetallic compounds of the bonding interface to improve the bonding strength, effectively reduce the resistivity, and increase the conductivity.
[0014] The U-shaped copper-aluminum composite transition plate of the present invention needs to be prepared by two explosions, and the key difficulty lies in the second explosion. In the second explosion, since the middle of the end face of the copper-aluminum composite plate is a copper interface, and the two sides are aluminum interfaces, the explosion is compounded by the explosion of copper and aluminum dissimilar metals to the explosion of aluminum and aluminum of the same material. Based on the different mechanical properties such as yield strength of the two substrates, the plastic deformation degree of the substrate during the explosion welding process is different, and different types of waveforms are obtained. The larger the waveform of the interface, the more holes and gaps there are, which weakens the bonding strength of the interface, and cracks are easily generated when the explosion load is too large. In order to solve this technical problem, the technical solution of the present invention adopts a gradient charge distribution method, gradually reducing the charge amount from the middle to the edge along the detonation direction, and detonating from the center of the short side of the aluminum plate to be composited so that the explosion load at each part of the composite plate remains basically unchanged, controlling the collision speed between the base and the composite plate, avoiding the large wave-shaped combination containing defects such as gaps and cavities caused by the melting of the metal due to excessive charge, reducing the degree of explosive strengthening of the substrate, reducing the deformation of the entire composite plate, and improving the bonding strength and stability of the composite plate. At the same time, test data showed that the amount of explosives can be reduced by about 10%, which not only reduces production costs but also reduces adverse impacts on the environment.
[0015] As a preferred solution, in 1) and 2), the height of the inner support is 3-5 mm. If the inner support is too high or too low, resulting in a gap that is too large or too small, it is more difficult for the gas in the gap to be discharged in time and completely. The inner support is, for example, a V-shaped aluminum sheet or an L-shaped aluminum sheet.
[0016] As a preferred solution, in 1) and 2), the thickness of the buffer pad is 0.5-2 mm; the buffer pad is a plastic film. The buffer pad can buffer the explosion load and protect the surface of the substrate.
[0017] As a preferred solution, in 1), the explosive is an expanded ammonium nitrate explosive, which is laid on the cushion with a thickness of 15 to 25 mm. If the amount of explosive is too much, it is easy to cause the melting of the metal to produce continuous intermetallic compounds and large wavy bonding interfaces with defects such as voids. If the amount of explosive is too little, the purpose of explosive compounding cannot be achieved. A further preferred expanded ammonium nitrate explosive is a mixture of ammonium nitrate and sodium perchlorate in a mass ratio of 3 to 5:1, and additionally added with 2 to 4 wt% of SP-80 emulsifier, 3 to 5 wt% of perlite and 7 to 12 wt% of iron powder.
[0018] As a preferred solution, in 2), the explosive is expanded ammonium nitrate explosive, which is laid on the cushion with a thickness of 30 to 35 mm in the middle and 26 to 28 mm at the edge, and the thickness of the explosive laid from the middle to the edge of the cushion decreases uniformly. Further preferably, the difference in thickness between the explosive laid in the middle and the edge of the cushion is generally 4 mm to 9 mm. If the amount of explosive is too much, it is easy to cause the melting of the metal to produce continuous intermetallic compounds and large wavy bonding interfaces with defects such as voids. If the amount of explosive is too little, the purpose of explosive composite cannot be achieved. By gradually reducing the charge thickness from the middle to the edge, the distribution of explosives on the composite plate is changed, so that the explosion load at each part of the composite plate remains basically unchanged, the collision speed between the base and the composite plate is controlled, damage to the composite interface is avoided, and the bonding strength and stability of the product are improved.
[0019] As a preferred solution, in 1), the thickness of the aluminum plate is 5-18 mm.
[0020] As a preferred solution, in 2), the thickness of the aluminum plate is 15-26 mm.
[0021] As a preferred solution, in 1), the average detonation velocity of the explosive is 1600-2400 m / s.
[0022] As a preferred solution, in 2), the average detonation velocity of the explosive is 2200-3600 m / s.
[0023] As a preferred solution, the annealing treatment condition is: 150±20℃, heat preservation for 1~2h. Annealing treatment can effectively eliminate the internal stress generated during explosive welding. The U-shaped copper-aluminum composite transition plate after heat treatment has excellent heating performance, which is close to pure copper and better than pure aluminum.
[0024] The present invention also provides a U-shaped copper-aluminum composite transition plate, which is obtained by the preparation method. The U-shaped copper-aluminum composite transition plate of the present invention has aluminum composites on three sides at one end, and in the process of copper-aluminum interface bonding, metallurgical bonding can be achieved at three interfaces to form a bite structure, with high bonding strength and higher product connection reliability. At the same time, its copper-aluminum interface is metallurgically bonded, with high bonding strength, low resistivity and good conductivity.
[0025] The present invention also provides an application of a U-shaped copper-aluminum composite transition plate, which is applied to aluminum and copper interface welding.
[0026] The U-shaped copper-aluminum composite transition plate of the present invention is used for aluminum and copper interface welding, especially for the transition connection between aluminum soft strips and copper soft strips, and has the advantages of stable quality, high reliability, material saving, easy installation and use, simple production process, etc. It can be widely used for the connection of metal aluminum and copper in graphitization furnaces, transformers and other devices, and achieves metallurgical bonding between metals, preventing electrochemical corrosion caused by direct connection between aluminum and copper metals and the occurrence of safety accidents. It can effectively solve the problem of multiple intermetallic compounds that are easily generated during traditional welding of copper and aluminum, causing fractures, and improve product quality and safety.
[0027] The preparation method of the U-shaped copper-aluminum composite transition plate of the present invention comprises the following specific steps:
[0028] Step 1: Use grinding and polishing equipment to grind and polish the metal interface of the copper plate and the aluminum plate to be composited, so that the interface to be composited completely reveals the metallic luster and the surface is flat and smooth;
[0029] Step 2: Metal plate assembly and explosive compounding: Place a number of evenly distributed inner supports between the copper plate and the aluminum plate, with a height of 3-5 mm, to ensure that the two plates are in the same horizontal position, the thickness of the upper and lower aluminum layers is 5-18 mm, and a 0.5-2 mm plastic film is laid on the composite aluminum, and a 15-25 mm thick expanded ammonium nitrate mixed explosive is laid on the plastic film for the first explosive compounding, and the first explosive compounding is detonated from the end of the aluminum plate to be compounded, with an average detonation velocity of 1600-2400 m / s; the assembled metal plate assembly is detonated by a detonating cap inserted in the end charge frame to realize the explosive compounding of the metal material assembly. The copper-aluminum composite plate subjected to the first explosive composite is used as the base layer, and a plurality of evenly distributed inner supports are placed on the composite side to install the composite aluminum metal, the thickness of the composite aluminum surface is 15-26 mm, and the interface to be composited needs to be polished to expose the metallic luster, and a 0.5-2 mm plastic film is laid on the back of the composite surface of the composite aluminum metal, and then a gradient charge distribution scheme is used on the buffer pad to gradually reduce the charge thickness from the middle to the edge, the charge thickness in the middle is 30-35 mm, and the charge thickness at the edge is 26-28 mm, and the thickness of the explosive laid from the middle to the edge of the buffer pad is uniformly reduced, so that the explosion load at each part of the composite plate remains basically unchanged, the collision speed between the base and the composite plate is controlled, and the second explosive composite is detonated from the midpoint of the short side of the composite surface of the aluminum plate, and the average explosion speed is 2200-3600 m / s, so as to obtain a U-shaped copper-aluminum composite plate;
[0030] Step 3: Flaw detection: The multi-layer composite board after explosive bonding is subjected to 100% UT testing;
[0031] Step 4: Heat treatment: Heat treatment is performed on the composite plate after flaw detection to eliminate the internal stress generated during explosive welding. Heat treatment process: the composite plate is heated to 150±20℃ with the furnace, kept warm for 1~2h and then cooled with the furnace. The U-shaped copper-aluminum composite transition plate after heat treatment has excellent heating performance, which is close to pure copper and better than pure aluminum.
[0032] Step 5: After leveling, nondestructive testing and trimming of the heat-treated composite plate, the surface is machined to the drawing requirements.
[0033] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0034] The U-shaped copper-aluminum composite transition plate provided by the present invention has a U-shaped structural design. Aluminum is composited on three sides of the end surface of the copper plate, so that metallurgical bonding can be achieved at three interfaces to form a bite structure, with high bonding strength and higher product connection reliability.
[0035] The U-shaped copper-aluminum composite transition plate provided by the present invention realizes aluminum composite on three sides of the end surface of the copper plate by adopting explosive composite and heat treatment methods, and has a high bonding rate at the copper-aluminum interface, high bonding strength and good electrical conductivity.
[0036] The preparation method of the U-shaped copper-aluminum composite transition plate provided by the present invention realizes aluminum composite on three sides of the end surface of the copper plate by adopting explosive composite and heat treatment methods, and the bonding rate of the copper-aluminum interface is high. At the same time, the intermetallic compounds of the bonding interface can be effectively controlled to achieve the purpose of improving the bonding strength, effectively reducing the resistivity, and increasing the conductivity. Compared with other existing composite methods, there are obvious technical advantages, and this method does not require expensive equipment and a large number of operators, and has fast molding, high efficiency, low cost, stable quality and excellent performance.
[0037] The U-shaped copper-aluminum composite transition plate provided by the present invention is applied to the interface welding of aluminum and copper, especially in circuit connection. The U-shaped copper-aluminum composite transition plate is used to perform transition connection between the aluminum soft strip and the copper soft strip. It has the advantages of stable quality, high reliability, material saving, convenient installation and use, simple production process, etc. It can be widely used for the connection of metal aluminum and copper in graphitization furnaces, transformers and other devices, to achieve metallurgical bonding between the metals, prevent electrochemical corrosion caused by direct connection between aluminum and copper metals, and prevent safety accidents. It can effectively solve the problem of multiple intermetallic compounds easily generated during traditional welding of copper and aluminum, causing fractures, and improve product quality and safety.
[0038] The resistivity of the U-shaped copper-aluminum composite transition plate provided by the present invention is close to that of pure copper and better than that of pure aluminum, indicating that the copper-aluminum composite material can replace pure copper as a conductive material, thereby achieving about 40% savings in copper materials by replacing copper with aluminum. Not only is the reliability higher, but the use of copper and aluminum is also greatly reduced, the process power consumption per ton of product is reduced by 30%, the investment cost and power consumption of production equipment construction are greatly reduced, the annual carbon reduction is greatly reduced, the energy-saving effect is remarkable, the overall price advantage is obvious, the cost performance is high, and it has significant social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the U-shaped copper-aluminum composite transition plate bonding interface in Example 4.
[0040] Figure 2 This is a schematic diagram of the U-shaped copper-aluminum composite transition plate structure.
[0041] Figure 3 This is a schematic diagram of the installation of the U-shaped copper-aluminum composite transition plate.
[0042] Figure 4 This is a physical picture of the U-shaped copper-aluminum composite transition plate.
[0043] Figure 5 This is a physical picture of the installation of the U-shaped copper-aluminum composite transition plate. DETAILED DESCRIPTION
[0044] The following specific examples are intended to further illustrate the present invention in detail, rather than to limit the scope of protection of the claims.
[0045] The expanded ammonium nitrate explosive used in the following specific embodiments is prepared by mixing ammonium nitrate and sodium perchlorate in a mass ratio of 4:1, and additionally adding 3wt% of SP-80 emulsifier, 4wt% of perlite and 10wt% of iron powder. Example 1
[0046] Step 1: Use grinding and polishing equipment to grind and polish the metal interface to be composited, so that the composite interface completely reveals the metallic luster and the surface is smooth and clean;
[0047] Step 2: Metal sheet assembly and explosive compounding: Place a number of evenly distributed inner supports (L-shaped aluminum sheets) between the metal sheets. The height of the supports is 3mm to ensure that the sheets are in the same horizontal position. The thickness of the upper and lower aluminum layers is 13mm. Lay a 1mm plastic film on the composite aluminum sheet. Lay a 15mm thick expanded ammonium nitrate mixed explosive on the plastic film for the first explosive compounding. The average explosive detonation velocity is 1800m / s. Detonate the explosives with the assembled metal sheet assembly through the detonating cap inserted in the end charge frame to achieve explosive compounding of the metal material assembly. The copper-aluminum composite plate used for the first explosive composite is used as the base layer. The composite interface needs to be polished to reveal the metallic luster. The composite aluminum metal is installed on the composite side by placing several evenly distributed 3mm high internal supports (L-shaped aluminum sheets). A 1mm plastic film is laid on the 25mm thick composite aluminum surface. Then, the thickness of the charge is gradually reduced from the middle to the edge on the plastic film for gradient distribution of explosives. The thickness of the charge in the middle is 35mm, and the thickness of the charge at the edge is 28mm. The thickness of the explosive laid from the middle to the edge of the buffer pad decreases evenly. The second explosive composite is detonated from the midpoint of the short side, and the detonation velocity of the explosive is 2500m / s.
[0048] Step 3: NDT: The multi-layer composite board after explosive cladding was tested by 100% UT, with an interface bonding rate of 90% and an interface shear strength of 47MPa.
[0049] Step 4: Heat treatment: Heat treatment is performed on the composite plate after flaw detection to eliminate the internal stress generated during explosive welding. Heat treatment process: the composite plate is heated to 150°C with the furnace, kept warm for 2 hours, and then cooled with the furnace.
[0050] Step 5: After leveling, nondestructive testing and trimming of the heat-treated composite plate, the surface is machined to the drawing requirements. Example 2
[0051] Step 1: Use grinding and polishing equipment to grind and polish the metal interface to be composited, so that the composite interface completely reveals the metallic luster and the surface is smooth and clean;
[0052] Step 2: Metal sheet assembly and explosive compounding: Place a number of evenly distributed inner supports (L-shaped aluminum sheets) between the metal sheets. The support height is 4mm to ensure that the sheets are in the same horizontal position. The thickness of the upper and lower aluminum layers is 13mm. Lay a 1mm plastic film on the composite aluminum sheet. Lay a 15mm thick expanded ammonium nitrate mixed explosive on the plastic film for the first explosive compounding. The detonation velocity of the explosive is 1600m / s. Detonate the explosive with the detonating cap inserted in the end charge frame to realize the explosive compounding of the metal material assembly. The copper-aluminum composite plate of the first explosive composite is used as the base layer. The composite interface needs to be polished to reveal the metallic luster. The composite aluminum metal is installed on the composite side by placing a number of evenly distributed 3mm high internal supports (L-shaped aluminum sheets). A 1.5mm plastic film is laid on the 25mm thick composite aluminum surface. Then, the thickness of the charge is gradually reduced from the middle to the edge on the plastic film to carry out gradient charge distribution. The second explosive composite is detonated from the midpoint of the short side. The thickness of the charge in the middle is 35mm, and the thickness of the charge at the edge is 28mm. The average explosion rate is 3000m / s.
[0053] Step 3: Flaw detection: The multi-layer composite board after explosive compounding was tested by 100% UT, with an interface bonding rate of 95% and an interface shear strength of 55Mpa.
[0054] Step 4: Heat treatment: Heat treatment is performed on the composite plate after flaw detection to eliminate the internal stress generated during explosive welding. Heat treatment process: the composite plate is heated to 160°C with the furnace, kept at this temperature for 2 hours, and then cooled with the furnace;
[0055] Step 5: After leveling, nondestructive testing and trimming of the heat-treated composite plate, the surface is machined to the drawing requirements. Example 3
[0056] The difference between this embodiment and embodiment 1 is that the thickness of the mixed explosive used in the first explosive composite is 25mm, and the detonation speed is 2400m / s; the thickness of the explosive in the middle of the second explosive composite is 35mm, the thickness of the explosive at the edge is 28mm, and the detonation speed is 3600m / s. The interface bonding rate of the composite plate obtained is 98.5%, and the interface shear strength is 62MPa. Example 4
[0057] The difference between this embodiment and embodiment 2 is that the thickness of the second explosion composite in the middle is 32mm, the thickness of the edge is 26mm, and the explosion speed is 3300m / s. The interface bonding rate of the composite plate is 99.6%, and the interface shear strength is 68MPa. The interface metallographic detection of the sample is carried out. The obtained bonding interface is slightly corrugated, which effectively avoids the generation of a large corrugated bonding interface. The intermetallic compounds are greatly reduced, and the bonding quality of the composite plate is further improved. No defects such as voids, cavities and cracks are found (as shown below). Figure 1 as shown).
[0058] Comparative Example 1
[0059] Other conditions are the same as those in Example 1, except that no buffer pad is placed on the aluminum alloy of the cladding plate. A large number of pits appear on the surface of the aluminum plate obtained by explosive composite. During the explosive welding process, the metal plate will instantly experience the impact of the high-speed moving detonation wave and explosion products and the effect of thousands of degrees of high temperature, causing the surface of the cladding material to be damaged and oxidized. The degree of this damage will increase with the increase of the intensity of the explosive. Placing protective materials such as buffer pads on the metal surface can buffer the explosion load and protect the cladding surface.
[0060] Comparative Example 2
[0061] The other conditions are the same as those in Example 1, except that the explosives for the first explosion composite are prepared at a detonation velocity of 1500 m / s and the explosives for the second explosion composite are prepared at a detonation velocity of 2000 m / s. Most of the unbonded areas appear, and the bonding strength of the local positions of the bonded areas detected is low. This is because there is an optimal collision velocity for explosive welding. If the collision velocity is too low, the composite energy between the metal plates is insufficient, and the gas is not fully discharged in time, thereby affecting the welding quality at the welding interface.
[0062] Comparative Example 3
[0063] Other conditions are the same as those in Example 1, with the only difference being that in the second explosion composite, the thickness of the middle portion is 40 mm, and the thickness of the edge portion is 35 mm. Samples were taken for interface metallographic examination, and the resulting bonding interface was large corrugated, and a large amount of intermetallic compounds appeared, and defects such as gaps, cavities, and cracks appeared in some areas. That is, too much charge and too high explosive detonation velocity will produce a larger detonation pressure, and the collision velocity increases to obtain a large wavy interface.
[0064] Application Examples
[0065] The copper-aluminum composite transition joint prepared in Example 4 was used in a company's first-phase 50kt / a high-end lithium-ion battery negative electrode material graphitization project. The two ends of the U-shaped copper-aluminum composite transition plate were welded with aluminum busbars and copper busbars (such as Figure 5 As shown), the assembly is then welded and installed on the graphitization furnace. In the application process of copper-aluminum composite transition joints, the effect is remarkable in terms of investment level, product quality, energy consumption, safe production and environment, reducing construction investment costs by more than 50 million yuan, increasing production capacity by more than 50%, reducing power consumption per ton of product by 30%, and increasing power factor by about 5%, achieving very satisfactory production and operation results.
Claims
1. A method for preparing a U-shaped copper-aluminum composite transition plate, characterized in that: The following steps are involved: 1) After grinding and polishing the upper and lower surfaces to be composited at one end of the copper plate and the surface to be composited of the aluminum plate, an aluminum plate is assembled with the upper and lower surfaces to be composited of the copper plate in the manner of assembling the surfaces to be composited opposite to each other, an internal support is provided between the copper plate and the aluminum plate to ensure that the surface to be composited of the copper plate and the aluminum plate are at the same horizontal position, a buffer pad is laid on the back of the surface to be composited of the aluminum plate, explosives are evenly laid on the buffer pad, and the first explosive composite is detonated from the end of the surface to be composited of the aluminum plate to obtain a copper-aluminum composite plate; 2) After the copper-aluminum end faces to be composited of the copper-aluminum composite plate and the surface to be composited of the aluminum plate are polished, the copper-aluminum end faces of the copper-aluminum composite plate are assembled with an aluminum plate in the manner of assembling the opposite faces of the surfaces to be composited, and an internal support is provided between the copper-aluminum end faces of the copper-aluminum composite plate and the aluminum plate to ensure that the copper-aluminum end faces of the copper-aluminum composite plate and the aluminum plate are at the same horizontal position, a buffer pad is first laid on the back of the surface to be composited of the aluminum plate, and then explosives are laid on the buffer pad in a gradient distribution method with the charge thickness gradually decreasing from the middle to the edge, and a second explosive composite is performed by detonating from the midpoint of the short side of the surface to be composited of the aluminum plate to obtain a U-shaped copper-aluminum composite plate; 3) Annealing the U-shaped copper-aluminum composite plate to obtain; in, In 1) and 2), the height of the inner support is 3-5 mm; In 1) and 2), the thickness of the cushion is 0.5-2 mm; 1), the explosive is expanded ammonium nitrate explosive, which is laid on the cushion with a thickness of 15 to 25 mm; The average detonation velocity of the explosive is 1600-2400 m / s; 1), the thickness of the aluminum plate is 5-18 mm; 2), the thickness of the aluminum plate is 15-26 mm; 2) The thickness of the explosives laid in the middle of the cushion is 30-35 mm, the thickness of the explosives laid at the edge is 26-28 mm, and the thickness of the explosives laid from the middle to the edge of the cushion decreases evenly; 2), the explosive is expanded ammonium nitrate explosive, and the average detonation velocity of the explosive is 2200-3600 m / s.
2. The method for preparing a U-shaped copper-aluminum composite transition plate according to claim 1, characterized in that: The buffer pad is a plastic film.
3. The method for preparing a U-shaped copper-aluminum composite transition plate according to claim 1, characterized in that: The annealing treatment conditions are: keeping warm at 150±20°C for 1-2h.
4. A U-shaped copper-aluminum composite transition plate, characterized in that: Obtained by the preparation method according to any one of claims 1 to 3.
5. The use of a U-shaped copper-aluminum composite transition plate according to claim 4, characterized in that: Applicable for welding between aluminum and copper.
Citation Information
Patent Citations
Copper aluminium cab apron that compounded
CN206461114U
Powdered emulsified explosive to process copper and aluminium plates explosion cladding method
CN101121219A
Copper-aluminium explosion composite electrical T type copper-aluminium bimetal binding clip and explosion welding method
CN101707295A